1995
DOI: 10.1523/jneurosci.15-07-05346.1995
|View full text |Cite
|
Sign up to set email alerts
|

Response of serotonergic caudal raphe neurons in relation to specific motor activities in freely moving cats

Abstract: Serotonergic neuronal responses during three specific motor activities were studied in nuclei raphe obscurus (NRO) and raphe pallidus (NRP) of freely moving cats by means of extracellular single-unit recordings. Responses to treadmill-induced locomotion were primarily excitatory, with 21 of 24 neurons displaying increased firing rates, directly related to treadmill speed. Individual regression analyses determined three response patterns: maximal activation at low speed (0.25 m/sec), augmentation of neuronal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
304
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(327 citation statements)
references
References 54 publications
22
304
1
Order By: Relevance
“…Differences in the basal serotonergic neuronal activity may explain why the peak magnitude and duration of changes in ventilation in the awake goat (+70%, 40 min, Turner et al 1997) and dog (+40%; Cao et al 1992) are somewhat lower than that recorded in anaesthetized rats (+70 to +100%, >60 min; Hayashi et al 1993;Bach and Mitchell, 1996). Similar findings are noted during sleep where the average firing rate of raphe neurons in cats decreased during slow wave and rapid eye movement sleep compared to alert waking state and correlated with increases in ventilation (Veasey et al 1995). Thus, decreased firing rate of the raphe neurons during NREM sleep relative to wakefulness may permit a greater dynamic range of increased caudal raphe neuron activity with episodic hypoxic stimulation.…”
Section: Ltf Of Genioglossusmentioning
confidence: 64%
See 1 more Smart Citation
“…Differences in the basal serotonergic neuronal activity may explain why the peak magnitude and duration of changes in ventilation in the awake goat (+70%, 40 min, Turner et al 1997) and dog (+40%; Cao et al 1992) are somewhat lower than that recorded in anaesthetized rats (+70 to +100%, >60 min; Hayashi et al 1993;Bach and Mitchell, 1996). Similar findings are noted during sleep where the average firing rate of raphe neurons in cats decreased during slow wave and rapid eye movement sleep compared to alert waking state and correlated with increases in ventilation (Veasey et al 1995). Thus, decreased firing rate of the raphe neurons during NREM sleep relative to wakefulness may permit a greater dynamic range of increased caudal raphe neuron activity with episodic hypoxic stimulation.…”
Section: Ltf Of Genioglossusmentioning
confidence: 64%
“…Given that LTF of hypoglossal nerve activity recorded in rats has been noted to be dependent on serotonin pathways Mitchell, 1996, Fuller et al 2001), the occurrence of GG LTF in non-snoring, non-flow limited individuals suggests that sleep, per se, may be a determinant of LTF. This may relate to the fact that medullary serotonergic neuronal activity is decreased during NREM sleep, and discharges at higher, nearly maximal levels during wakefulness (Veasey et al 1995). Differences in the basal serotonergic neuronal activity may explain why the peak magnitude and duration of changes in ventilation in the awake goat (+70%, 40 min, Turner et al 1997) and dog (+40%; Cao et al 1992) are somewhat lower than that recorded in anaesthetized rats (+70 to +100%, >60 min; Hayashi et al 1993;Bach and Mitchell, 1996).…”
Section: Ltf Of Genioglossusmentioning
confidence: 97%
“…However, modulation probably also results from the more rapid and precise junctional synaptic transmission. Many monoaminergic neurons are rhythmically active during locomotion (Jacobs and Fornal 1995;Veasey et al 1995) and noradrenergic fibers and boutons have been found in close proximity to locomotoractivated spinal neurons (Johnson et al 2002). This could account for the rhythmic modulation of noradrenergic-and serotonergic-sensitive (Bras et al 1990;Noga et al 1992Noga et al , 1995b) group II muscle afferent-evoked field potentials recorded in the mid-lumbar segments during fictive locomotion (Perreault et al 1999).…”
Section: Functional Significance Of Release Patternsmentioning
confidence: 99%
“…Moreover, the time to exhaustion is decreased by serotonin receptor agonists and increased by serotonin antagonists (18). It was also demonstrated that the activity of the raphe-spinal neurons correlates with the motor activity, suggesting that 5-HT is released as a function of motor output (19,20). Finally, spinal MNs are densely innervated by serotonergic synaptic terminals (21,22).…”
mentioning
confidence: 97%